Seeds of change - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Here are three handy 'how to' manuals on producing seeds for the market, written for individual farmers, community groups, local NGOs and schools lacking experience or formal training in seed production.